2004
DOI: 10.1007/s10499-004-5745-7
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory trials on the effects of different diets on growth and survival of the common whelk, Buccinum undatum L. 1758, as a candidate species for aquaculture

Abstract: Newly hatched juvenile Buccinum undatum can be reared under laboratory conditions. Good growth was achieved when juveniles were fed on combined diets (blue mussel, cod, and fish pellets). Juveniles reached shell heights of 33.0 AE 4.2 mm, 26.9 AE 3.8 mm, 23.2 AE 2.2 mm, and 20.1 AE 1.6 mm, after 14 months of feeding on a combined diet, blue mussel, cod, and fish pellets, respectively under ambient sea temperature and salinity. After 14 months juveniles fed blue mussel had the highest survival rates (67%) follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…However, growth performance was reduced at 75% level of fish meal protein replacement by poultry by-product meal, dueto deficiencies of lysine and methionine. Nasution and Roberts [18] showed that juvenile common whelks, Buccinum undatum, fed on blue mussels had the highest survival rate, followed by those fed on a combination of other experimental diets, cod waste and fish-feed pellets. In addition, this study indicated that the body composition of snails was affected by the replacement of fish meal with PBM meals.…”
Section: Discussionmentioning
confidence: 99%
“…However, growth performance was reduced at 75% level of fish meal protein replacement by poultry by-product meal, dueto deficiencies of lysine and methionine. Nasution and Roberts [18] showed that juvenile common whelks, Buccinum undatum, fed on blue mussels had the highest survival rate, followed by those fed on a combination of other experimental diets, cod waste and fish-feed pellets. In addition, this study indicated that the body composition of snails was affected by the replacement of fish meal with PBM meals.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing demand for gastropods in the international market as an important commercial fishery commodity has occurred only during the recent decades as a recognition to their nutritional qualities. Recently there has been a tremendous increase in the market value of the meat of C. ramosus, and it has evolved as a potential candidate for sea farming (Nasution and Roberts, 2004). However, structured information concerning the nutritional value of this predominantly available muricid gastropod is unprecedented, except for a short report on its proximate analysis (Ramesh and Ayyakkannu, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Buccinum undatum is an important commercial species, providing locally valuable fisheries in several areas around the North Atlantic including the UK, the USA and Canada [44], [45]. Demand for this species is continuously increasing globally (Department of Marine Resources www.maine.gov/dmr/rm/whelks.html) and it has been suggested as an aquaculture candidate [46]. It has a close taxonomic relationship with several deep-sea species, for example Buccinum abyssorum, Beringius turtoni, Belomitra quadruplex [47] and Buccinum thermophilium [37].…”
Section: Methodsmentioning
confidence: 99%